Review of Pool Boiling Enhancement Techniques - Osamah Altotanje; Nabeel Abdulrazzaq (NTU Journal of Engineering and Technology)
Many industrial applications recently are utilizing from the pool boiling to treat heat, including power plants, cooling and refrigeration  applications, and electronics cooling applications like data centers. The high efficiency of pool boiling is becoming very important to improve and develop systems performance and to lessen the fuel and energy loss or consumption. This literature review gathers the existing knowledge as possible on the pool boiling enhancement techniques. Paying attention on the challenges and development associated with these techniques. The examination involves studying basic principles of pool boiling focusing on factors like heat transfer rate and the technical specifications for surface and fluids. Then, it goes deeper reviewing the methods of enhancement, including surface treatment methods, surface modification and liquid physical properties. The goal of this review is to propose as a valuable resource for researchers, engineers, and students seeking a comprehensive understanding of the current state of pool boiling enhancement techniques. By strengthen diverse research findings and identifying gaps in knowledge, this review contributes to the ongoing pursuit of more efficient and sustainable heat transfer solutions for diverse industrial applications.The abstract needs to summarize the content of the paper.